Optimization of non-invasive glucose monitoring accuracy using an optical sensor - Smailov, Nurzhigit; Zilgarayeva, Aliya; Pavlov, Sergii; Turusbekova, Balzhan; Sabibolda, Akezhan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
The development of non-invasive blood glucose monitoring technologies is progressing steadily, largely due to advancements in optical sensor systems. These systems assess physiological data by analyzing how light interacts with biological tissues. A common technique, near-infrared spectroscopy, typically utilizes wavelengths such as 500 nm, 970 nm, 1400 nm, and 1900 nm, selected for their enhanced responsiveness to glucose levels at varying tissue depths. In experimental settings, this method has demonstrated the ability to generate electrical signals that correlate with glucose concentrations, supporting its potential for accurate glucose tracking. The technique adheres to both detection and precision standards, particularly at higher glucose concentrations, making it a strong candidate for next-generation monitoring solutions. The study also outlines future objectives, including improving sensor accuracy, reducing device size, and enabling seamless integration with both clinical and home-based healthcare systems. Moreover, efforts to minimize interference and signal distortions are explored as part of the broader aim to refine system reliability.